Effects of extreme weather events and large scale factors in the population of Crangon crangon (L.1758) in the Mondego estuary - Dinis, David Garrido (2011)
Dissertação de mestrado em Ecologia Aplicada, apresentada à Faculdade de Ciências e Tecnologia da Universidade de Coimbra